Effects of nutrient intake, surgery, sepsis, and long term administration of steroids on muscle function. Issue 6553 (18th October 1986) - Brough, W; Horne, G; Blount, A; Irving, M H; Jeejeebhoy, K N
Abstract : The stimulated contraction-relaxation characteristics of the adductor pollicis muscle were used to assess nutritional state in patients and healthy controls. In both groups insufficient nutrition resulted in abnormal muscle function. The ratio of force of contraction at 10 Hz to that at 20 Hz yielded the best combination of sensitivity (87%) and specificity (82%). Sepsis resulted in abnormal muscle function, but the changes were easily distinguishable from those in subjects taking an inadequate diet. Long term administration of steroids, trauma, and surgery had no effect on muscle function. A prospective study of 11 malnourished patients with abnormal muscle function showed that all variables of muscle function returned to normal values with total parenteral nutrition. This reversal correlated significantly with the duration of parenteral nutrition and occurred before any change in anthropometric variables or plasma albumin concentration. Muscle function studies are sensitive and specific indicators of malnutrition; results depend on energy intake but are not influenced by administration of steroids, trauma, or surgery.